2019
DOI: 10.1186/s13756-019-0630-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of Citrobacter freundii strains coproducing OXA-48 and VIM-1 carbapenemase enzymes isolated in leukemic patient in Spain

Abstract: BackgroundThe emergence of carbapenemase-producing (CP) Citrobacter freundii poses a significant threat to public health, especially in high-risk populations. In this study, whole genome sequencing was used to characterize the carbapenem resistance mechanism of three C. freundii clinical isolates recovered from fecal samples of patients with acute leukemia (AL) from Spain.Materials and methodsTwelve fecal samples, collected between 2013 and 2015 from 9 patients with AL, were screened for the presence of CP str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…26 Whereas various MBL genes, including bla NDM-1 , bla VIM-1 , bla VIM-4 , and bla IMP-8 , in association with other carbapenemase genes (non-MBL) particularly bla OXA-48 and bla KPC-2 have been detected in C. freundii. [27][28][29][30] Likewise, we report in our study the second detection in the world of the bla VIM-48 gene, which was first found in Pseudomonas putida isolated from chicken in China. 31 It has been reported that VIM-48 increases the enzymatic activity, thermostability, and resistance to carbapenems.…”
Section: Resultssupporting
confidence: 67%
“…26 Whereas various MBL genes, including bla NDM-1 , bla VIM-1 , bla VIM-4 , and bla IMP-8 , in association with other carbapenemase genes (non-MBL) particularly bla OXA-48 and bla KPC-2 have been detected in C. freundii. [27][28][29][30] Likewise, we report in our study the second detection in the world of the bla VIM-48 gene, which was first found in Pseudomonas putida isolated from chicken in China. 31 It has been reported that VIM-48 increases the enzymatic activity, thermostability, and resistance to carbapenems.…”
Section: Resultssupporting
confidence: 67%
“…Interestingly, there are eleven isolates in this study that carried two different types of carbapenemase genes, three of them were from 2015. The uncommon co-carriage of genes encoding different classes of carbapenemases genes were already described in the literature and reported in the western region of Saudi Arabia [35–38]. As migration and population mobility are increasingly important determinants of infection transmission, these issues will require greater policy attention at the multilateral level.…”
Section: Discussionmentioning
confidence: 98%
“…The study of Arana et al also highlighted several remarkable findings, such as clonal and polyclonal dissemination of C. freundii across different geographical areas and hospitals. OXA-48 and VIM-1 enzymes encoded were also detected in C. freundii from patients with acute leukemia in Spain [ 45 ].…”
Section: Discussionmentioning
confidence: 99%